ÖZBEKİSTAN TARİHİ (1917-1991) - KARA, FÜSUN (Fırat Üniveristesi, 1999)
Batı Türkistan'daki Türklerin büyük bir çoğunluğunu teşkil eden Özbekler, Özbekistan Cumhuriyetinde yaşamak. adırlar. Komşu Cumhuriyetlerde yaşayan Özbeklerin sayısı azınlıktadır. Özbek tabiri etnolojik bir terim olmayıp Cengiz Han'ın en büyük oğlu Cuci Han'ın hanedanında gelmiş olan Özbek Hanın ( 1312-134 C. adına izafeten verilen politik bir terimdir. 14 ve 15. Yüzyıllarda Özbekler Müslüman Türkler olarak anılmaya başladılar. 1924 yılında Özbekistan, SSC3 bünyesine dahil edildi ve Özbek SSC ismini aldı. Özbek tarihinde Anti. Rus ve Ant i Sovyet olarak nitelendirilen Basmacı Hareketi ortaya çıktı ve geniş bir alana yayıldı. 1917 yılında başlayan Basmacı Hareketi 1931 yılına kadar devam etti. Sovyet döneminde Özbek kültürel hayatındaki en önemli değişiklik 1930 yılında Arap alfabesinden La t ir. alfabesine, 1940 yılında Latin alfabesinden Kril Alfabesine geçilmesi olmuştur. 31 Ağustos 1991 tarihinde Özbekistan Cumhuriyeti bağımsızlığını ilan etti. Ve bağımsız Özbekistan Cumhuriyeti kuruldu. Anahtar Kelimeler: SSCB, Özbek SSC, Fergana Vadisi, Basmacı Hareketi Taşkent, îslam Kerimov.

The Uzbeks are the most numerous Turks in Turkestan and dwell in the Republic of Uzbekistan with many small settlements in neighboring republics. The word Uzbek is not is derived ethnological term but a political one, and is derived from Uzbek Khan (1312-1340), of the house of Juchi Chengiz eldest son. Early in the fourteenth and fifteenth centuries Uzbek began to mean Moslem Turks, as Uzbek Khan was a great propagator of Islam. In 1924 this Republic was, transformed into a Socialist Republic, and was formally included within the part of the Union of Soviet Socialist Republics as the Uzbek SSR. The Basmachi movement was a series cf anti -Russian and anti-Soviet uprisings by Turkestanis which at times embraced great regions and large numbers of participants. It started in 1917, and with some interoptions continued until 1931. The traditional Arabic Script of the Uzbek language was replaced by a modified Arabic script in 1923. A Latin alphabet was made official in Uzbeksitan in 1930; In 1940 and 1941 the Latin script was replaced by the one still in use, based on the Cyrillic alphabet with additional symbols. It was August 31, 1991 when the Supreme Council of the Republic of Uzbekistan passed the Resolution "on the proclamation of state Independence of the Republic of Uzbekistan" on the Law on the foundations of State Independence of the Republic of Uzbekistan. Key words: Union of Soviet Socialist Republics, Uzbek SSR, Fergana Valley, Basmachi Movement. Tashkent, Islam Kerimov.
History of Uzbekistan (1917-1991)
Keywords: Tarih; History